Coronoidectomy as a treatment for mandibular immobility caused by fracture of the coronoid process in three horses. (26th November 2020) - Magri, C.; Schramme, M.; Nottrott, K.; Schweizer‐Gorgas, D.; Segard, E.; Kelly, G.; Schumacher, J.
Summary: This report describes the history, clinical signs and treatment of three horses suffering from deviation and immobility of the mandible resulting from fracture of a coronoid process of the mandible. Deviation and immobility resulted from impingement of a callus between the temporal bone and zygomatic arch. Fracture of the coronoid process was identified by using radiography, ultrasonography, computed tomography or a combination of two or more of these imaging modalities. Osteoarthritis of the ipsilateral temporomandibular joint of two horses was identified. All horses were treated by excising the fractured coronoid process, and two were also treated by excising the diseased ipsilateral mandibular condyle. All horses were able to open their mouth more widely immediately after surgery. One horse experienced moderate post‐operative haemorrhage, and all had severe shear mouth. Shear mouth was ameliorated gradually over many months by rasping dental overgrowths. Mandibular movement of all horses improved, allowing efficient mastication of feed. One horse was able to be used as a showjumper, one horse was sold at Thoroughbred yearling sales and was lost to follow‐up, and one horse died from an unrelated gastrointestinal disease 10 months after mandibular coronoidectomy and condylectomy.